Halal and Islamic Entrepreneurship in Sustainable Tourism Destinations: A Systematic Literature Review of Trends and Future Research Directions - Azkarni Kamal; Asmar Yulastri; Yuliana Yuliana; Yudha Aditya Fiandra (Brilliant International Journal Of Management And Tourism, 2026)
A comprehensive literature review to investigate halal and Islamic businesses in sustainable tourism destinations. The study focuses on a growing but fragmented literature linking halal tourism, Islamic entrepreneurship, MSME innovation, digital capacity, community empowerment, and sustainable destination competitiveness. Although halal tourism has received increasing academic attention, previous studies have largely focused on the tourist experience, halal attributes, Islamic marketing, certification, and sustainability as separate themes, so the entrepreneurial mechanisms underlying sustainable halal tourism have not been satisfactorily synthesized. This study uses a systematic literature review technique complemented by bibliometric and thematic analysis of Scopus indexed articles. According to the data, research on halal and Islamic entrepreneurship in sustainable tourism destinations increased between 2017 and 2025 with Indonesia, Malaysia, and Thailand making significant contributions. Based on thematic analysis, the main topics include sustainability, tourism development, innovation, community-based tourism, and sustainable entrepreneurship, while halal and Islamic entrepreneurship are still underrepresented in mainstream sustainable tourism research. The study concludes that halal and Islamic entrepreneurship should be positioned not only as business activities in accordance with religious teachings, but also as an ethical and entrepreneurial ecosystem that connects Islamic values, MSME innovation, digital transformation, community empowerment, halal assurance, and sustainable destination governance. This research contributes by presenting a comprehensive research agenda to expand halal tourism as a model for inclusive destination development.